2011
DOI: 10.1254/jphs.10264fp
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Orexin-A on Post-ischemic Glucose Intolerance and Neuronal Damage

Abstract: Abstract. Orexin-A is a newly identified neuropeptide expressed in the lateral areas of the hypothalamus that plays a role in various physiological functions, including regulation of glucose metabolism. We have previously reported that the development of post-ischemic glucose intolerance is one of the triggers of ischemic neuronal damage. Therefore, the aim of this study was to determine the effects of orexin-A on the development of post-ischemic glucose intolerance and ischemic neuronal damage. Male ddY mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 36 publications
(40 reference statements)
1
48
0
Order By: Relevance
“…These results suggest that BDNF in the central nervous system is an important regulator of glucose metabolism in peripheral organs via "inter-tissue communication", and the hypothalamus is an essential brain region that directs this system (24). Furthermore, our previous observation showed that hyperglycemia or a decrease in whole-body insulin sensitivity after cerebral ischemia was due to decreased hepatic InsR expression and activity and to the induction of PEPCK and G6Pase (16). Therefore, it is possible that post-ischemic glucose intolerance can be improved through suppression of hypothalamic BDNF loss caused by cerebral ischemic stress.…”
Section: Discussionmentioning
confidence: 73%
“…These results suggest that BDNF in the central nervous system is an important regulator of glucose metabolism in peripheral organs via "inter-tissue communication", and the hypothalamus is an essential brain region that directs this system (24). Furthermore, our previous observation showed that hyperglycemia or a decrease in whole-body insulin sensitivity after cerebral ischemia was due to decreased hepatic InsR expression and activity and to the induction of PEPCK and G6Pase (16). Therefore, it is possible that post-ischemic glucose intolerance can be improved through suppression of hypothalamic BDNF loss caused by cerebral ischemic stress.…”
Section: Discussionmentioning
confidence: 73%
“…We found that hepatic InsR and p-InsR protein expression levels were significantly lower in animals from the MCAO group than in the sham group on day 1 after MCAO ( Fig. 2: D and E) (50). In addition, in skeletal muscle, the InsR and p-InsR levels tended to be lower in the MCAO group than in the sham group (50).…”
Section: Possible Mechanisms Of Impaired Insulin Sensitivitymentioning
confidence: 80%
“…After ischemic stroke, we have demonstrated that hepatic PEPCK and G6Pase levels are significantly higher in the MCAO group than in the sham group (Fig. 2: F and G) (50). Hence, postischemic hyperglycemia or decrease in whole-body insulin sensitivity after ischemic stroke may be due to decreased hepatic InsR expression and to upregulation of gluconeogenesis (42).…”
Section: Possible Mechanisms Of Impaired Insulin Sensitivitymentioning
confidence: 85%
See 2 more Smart Citations